The Country Responsibilities of Oil Pipe Leakage - Kinanti Sekarayu; Nur Azizah Hidayat (Justitia Jurnal Hukum, 2020)
There is a fact that the pollution of the marine environment in the bay region of Balikpapan is caused by a ship anchor that hit and is related to the oil refinery pipes at the sea floor. The purpose of this legal research is to find out what forms of liability must be given by the parties concerned and what legal mechanism to use in resolving the case. First, forms of state responsibility for the leaking of oil refineries owned by PT. Pertamina is in the form of compensation, restoring and overcoming pollution of the marine environment. Second, the mechanism used by PT. Pertamina and the MV Ever Judger Ship can go through litigation and non-litigation channels. The Indonesian government should be able to affirm the prevailing laws and regulations so that those who commit pollution are responsible for resolving environmental disputes.Keywords: Environmental Pollution, Liability form, Sticky Settlement Mechanism